Queer Renaissance historiography: backward gaze - Nardizzi, Vin; Guy-Bray, Stephen ca. 20./21. Jh.; Stockton, William (Queer interventions, 2009)
Queer renaissance historiography : backward gaze / Stephen Guy-Bray, Vin Nardizzi, and Will Stockton -- A hundred years of queering the Renaissance / Will Fisher -- Beyond sodomy : what is still queer about early modern queer studies? / Goran Stanivuković -- "Let it suffise" : sexual acts and narrative structure in Hero and Leander / James M. Bromley -- Diana's band : safe spaces, publics, and early modern lesbianism / Jennifer Drouin -- Women's secretaries / Julie Crawford -- The touch of office : supernumerary economies and the Tudor public figure / Laurie Shannon -- Grafted to Falstaff and compounded with Catherine : mingling Hal in the second tetralogy / Vin Nardizzi -- Andrew Marvell and sexual difference / Stephen Guy-Bray -- Sexuality and society in the poetry of Katherine Philips / Graham Hammill -- Adam and Eve and the failure of heterosexuality / Will Stockton -- Afterword : period cramps / Madhavi Menon